MANAGEMENT OF NEUROGENIC BLADDER DYSFUNCTION IN POST-STROKE PATIENTS: A SYSTEMATIC REVIEW WITH COMPARISON OF EVIDENCE-BASED INTERVENTIONS (2015-2025) - Decroli, Rezeki Penta; Gemilang, Bayu (SINERGI : Jurnal Riset Ilmiah, 2025)
Introduction: Neurogenic bladder dysfunction constitutes a significant complication following stroke, affecting 40-60% of hospitalized stroke patients with substantial impacts on quality of life and rehabilitation outcomes. Aim: This research aims to systematically evaluate the efficacy, safety, and clinical effectiveness of various pharmacological, rehabilitative, and neuromodulatory approaches for managing neurogenic bladder dysfunction in post-stroke patients based on recent evidence (2015-2025). Methods: A systematic review was conducted using PubMed Central database (January 2015 - October 2025). Search query: (“stroke” OR “cerebrovascular accident” OR “brain infarction” OR “intracranial hemorrhage”) AND (“urinary incontinence” OR “neurogenic bladder” OR “lower urinary tract symptoms”) - (“post-stroke” OR “post-acute stroke”) AND (“bladder dysfunction” OR “detrusor overactivity” OR “urgency incontinence”) - (“stroke rehabilitation”) AND (“continence management” OR “urinary symptoms”)Inclusion criteria: peer-reviewed studies with open access, focus on post-stroke urinary dysfunction, English language, outcome data available. Nine publications were identified and analyzed. Results: Nine peer-reviewed publications were identified including comprehensive reviews, systematic reviews, randomized controlled trials, feasibility studies, and clinical research. Behavioral interventions (timed voiding, bladder training, pelvic floor muscle training) demonstrated 60-70% efficacy as first-line management with superior efficacy compared to pharmacological treatment alone. Physical rehabilitation approaches showed significant effectiveness. Neuromodulation (TTNS/PTNS) showed 50-75% efficacy with adverse events less than 5%. Electric stimulation combined with behavioral interventions showed enhanced outcomes. Upper urinary tract protection and individualized treatment plans are critical management considerations.Conclusion: Management of neurogenic bladder dysfunction in post-stroke patients requires an individually tailored treatment plan integrating behavioral techniques, lifestyle interventions, and pharmacological options. Behavioral management should constitute first-line therapy, with neuromodulation and specialized rehabilitation serving as effective alternatives. Proper diagnosis through urodynamic assessment is essential, and bladder rehabilitation programs dependent on patient cooperation and independence are crucial for success.